1993
DOI: 10.1111/j.1365-3164.1993.tb00184.x
|View full text |Cite
|
Sign up to set email alerts
|

A Blinded Comparison of the Efficacy of Daily and Twice Daily Trimethoprim‐Sulfadiazine and Daily Sulfadimethoxine‐Ormetoprim Therapy in the Treatment of Canine Pyoderma

Abstract: Abstract— In a blinded trial to determine the efficacy of potentiated sulfa drugs in the treatment of canine pyoderma, 50 dogs with superficial pyoderma were randomly assigned to receive either once or twice daily trimethoprim‐sulfadiazine (30mg.kg‐1) or once daily sulfadimethoxine‐ormetoprim (55mg.kg‐1 on the first day, then 27.5 mg.kg‐1 thereafter). Dogs were evaluated prior to antibiotic therapy. Clinical efficacy of the antibiotic was assessed after 3 weeks of antibiotic therapy and, if needed, after 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 12 publications
(15 reference statements)
4
32
1
1
Order By: Relevance
“…Most studies evaluating the efficacy of AMDs indicate that SBF infections are resolved after 3 weeks or more of systemic AMD treatment; rapid improvement over the first 1-2 weeks is typically observed, but resolution of all lesions and prevention of rapid recurrence of disease requires 3-6 weeks of treatment. [17][18][19][20][21][22]28 Although there is no significant difference in the likelihood of resolution of MSSP after 3-4 weeks of systemic AMD treatment compared with MRSP infections, it has been reported that MRSP infections took longer to treat compared with MSSP infections. 60 In a minority of patients, resolution of lesions may be achieved with 2 weeks of systemic AMDs.…”
Section: Systemic Antimicrobial Therapymentioning
confidence: 99%
“…Most studies evaluating the efficacy of AMDs indicate that SBF infections are resolved after 3 weeks or more of systemic AMD treatment; rapid improvement over the first 1-2 weeks is typically observed, but resolution of all lesions and prevention of rapid recurrence of disease requires 3-6 weeks of treatment. [17][18][19][20][21][22]28 Although there is no significant difference in the likelihood of resolution of MSSP after 3-4 weeks of systemic AMD treatment compared with MRSP infections, it has been reported that MRSP infections took longer to treat compared with MSSP infections. 60 In a minority of patients, resolution of lesions may be achieved with 2 weeks of systemic AMDs.…”
Section: Systemic Antimicrobial Therapymentioning
confidence: 99%
“…2,5,17,22 SDM/ OMP has been recommended for treatment of a variety of skin infections ranging from skin-fold pyoderma to deep pyoderma with furunculosis. 13,17 A concern with the use of this product in the treatment of deep pyoderma is the risk of adverse side-eects such as keratoconjunctivitis sicca and hypothyroidism when treatment is required beyond 21 days.…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…The recommended frequency of administration varies with the type of sulphonamide and the sensitivity of the organism against which the drug is being # 1999 Blackwell Science Ltd, Veterinary Dermatology, 10, 205±215 There is considerable controversy concerning the frequency of administration of SDZ/ TMP and SMX/TMP. 5±7, 13 The veterinary product SDZ/TMP is labelled for once-daily administration in dogs and horses, however many clinicians believe the drug is more ecacious if given twice daily regardless of whether they are using SDZ/TMP or SMX/TMP. 4±7 Once-daily dosing of SDZ/TMP at 30 mg kg 71 orally allows concentrations of trimethoprim to fall below therapeutic levels, but concentrations of sulphadiazine are maintained at levels that are ecacious against sensitive organisms throughout the dosing interval.…”
Section: Frequency Of Administrationmentioning
confidence: 99%
See 2 more Smart Citations